Luminal hypertonicity and acidity modulate colorectal afferents and induce persistent visceral hypersensitivity - La, Jun Ho (2012)
Carbohydrate malabsorption such as in lactose intolerance or enteric infection causes symptoms that include abdominal pain. Because this digestive disorder increases intracolonic osmolarity and acidity by accumulation of undigested carbohydrates and fermented products, we tested whether these two factors (hypertonicity and acidity) would modulate colorectal afferents in association with colorectal nociception and hypersensitivity. In mouse colorectum-pelvic nerve preparations in vitro, afferent activities were monitored after application of acidic hypertonic saline (AHS; pH 6.0, 800 mosM). In other experiments, AHS was instilled intracolonically to mice and behavioral responses to colorectal distension (CRD) measured. Application of AHS in vitro excited 80% of serosal and 42% of mechanically-insensitive colorectal afferents (MIAs), sensitizing a proportion of MIAs to become mechanically sensitive and reversibly inhibiting stretch-sensitive afferents. Acute intracolonic AHS significantly increased expression of the neuronal activation marker pERK in colon sensory neurons and augmented noxious CRD-induced behavioral responses. After three consecutive daily intracolonic AHS treatments, mice were hypersensitive to CRD 4-15 days after the first treatment. In complementary single fiber recordings in vitro, the proportion of serosal class afferents increased at day 4; the proportion of MIAs decreased, and muscular class stretch-sensitive afferents were sensitized at days 11-15 in mice receiving AHS. These results indicate that luminal hypertonicity and acidity, two outcomes of carbohydrate malabsorption, can induce colorectal hypersensitivity to distension by altering the excitability and relative proportions of colorectal afferents, suggesting the potential involvement of these factors in the development of abdominal pain.